Effects of Sediment Transport on Hydraulic Structures - Hrissanthou, Vlassios (IntechOpen, 2015)
Sediment transport is a significant part of the scientific area of river hydraulics. Therefore, the first section of the present book presents effects of sediment transport on hydraulic structures, that concern alluvial channel hydraulics. The second section refers to a serious consequence of river sediment transport, namely reservoir sedimentation. Sediment transported in a river originates from the corresponding basin, that is eroded by rainfall water. Hence, the quantification of soil erosion is also addressed in the second section. While soil erosion is the original physical process that causes reservoir sedimentation, the latter process may increase coastal erosion in case that the river feeding the reservoir, discharges its water into the sea. So, the effect of reservoir sedimentation on coastal erosion is further treated in the second section. Finally, the third section of the book is dedicated to the phenomenon of local scour around bridge piers, in particular the conditions of ice cover.